Lactic acid fermentation in alkaline conditions using enterococcus faecalis - Yeoh, Hui Di (University Malaysia Sarawak, UNIMAS., 2013)
Enterococcus faecalis was used to perform lactic acid fermentation (LAF) in hydrolyzed sago starch (HSS). LAF was studied in alkaline condition which was pH 8 using batch fermentation (BF) modes. From the study, this bacteria can considered as thermo tolerant due to its ability to growth well at 37°C and up to 48 °C and survive at pH 8. BF mode using HSS was performed to study the efficiency in productivity in LAF. The fermentation was performed in 3 L jar fermenter with a working volume of 2 L using HSS and yeast extract as carbon and nitrogen sources respectively. In addition, the kinetics of lactic acid production, glucose consumption, and NaOH consumption for each fermentation were analyzed during the BF. The highest LA production in the fermentation process was 92.52 g/L, with the conversion at range of 92%. Therefore, we can conclude that this isolated strain has potential to be used for industrial application in LA production.